FRI0180 Correlation Between Clinimetric Approach and German US7 Score in Rheumatoid Arthritis Patients Treated with Tocilizumab: A Pilot Study. (9th June 2015) - Terenzi, R.; Santoboni, G.; Bartoloni, E.; Alunno, A.; Luccioli, F.; Gerli, R.
Abstract : Background: Tocilizumab (TCZ) is a humanized monoclonal antibody against interleukin (IL)-6 receptor employed in rheumatoid arthritis (RA). The inhibition of acute phase reactant liver production is associated with rapid normalization of C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR), often predating synovitis improvement. Thus, ESR and CRP are not suitable to assess drug efficacy. Joint ultrasonographic (US) examination is commonly employed to detect RA subclinical synovitis. However, US assessment of the whole articular sites may be time consuming. To overcome such limitation, a novel US score, the German US7 score, has been recently proposed as rapid method to assess synovitis, tenosynovitis, power Doppler (PD) signal and erosions by grey scale (GS) in seven joints. Objectives: Since the strong effect of TCZ on acute phase reactants may underestimate disease activity, we investigated German US7 usefulness in detecting subclinical synovitis in TCZ-treated patients. Methods: Sixteen RA patients diagnosed according the EULAR/ACR 2010 classification criteria and treated with TCZ since at least 3 months were enrolled. Disease activity was evaluated by DAS28 and HAQ. German US7 score assessment was performed by two blinded investigators (Esaote myLab 70; linear probe 10-18 Mhz). The following sites of the clinically dominant hand and foot were evaluated: wrist, 2nd and 3rd metacarpophalangeal and proximal interphalangeal, and 2nd and 5th metatarsophalangeal joints. Details of the score are provided in Table 1 . Inter-observer agreement was very high (Cohen's κ=0.9). Spearman correlation coefficient (rho, ρ) was assessed to evaluate correlation between clinic parameters, laboratory data and domains of German US7 score. Results: As shown in Table, GSUS synovitis significantly correlated with DAS28-ESR (ρ=0.557; p<0.05), DAS28-CRP (ρ=0.721; p<0.019 and HAQ (ρ=0.634; p<0.01). GSUS tenosynovitis correlated with DAS28-ESR and DAS28-CRP (ρ=0.726; p<0.01 and ρ=0.668; p<0.01, respectively). GSUS erosions correlated with DAS28-ESR (ρ=0.535; p<0.05). When each DAS28 item was considered separately, tender and swollen joint number correlated with GSUS synovitis (ρ=0.744; p<0.001 and ρ=0.605; p<0.01, respectively), GSUS tenosynovitis (ρ=0.626; p<0, 01 and ρ=0.527 p<0.05, respectively) and PDUS synovitis (ρ=0.488; p<0.05 and ρ=0.577; p<0.05, respectively). No association between ESR and CRP and German US 7 score domains was observed. Conclusions: The present study suggests that German US7 score is a rapid tool to assess subclinical disease activity in RA patients receiving TCZ where ESR and CRP are not suitable to assess drug efficacy. US evaluation of TCZ-treated patients correlates with changing of clinical parameters, is able to detect subclinical activity and represents a prognostic parameter for new erosion development. In addition, our data, showing a strong correlation between number of tender and swollen joints and presence of PD signal, further support PD usefulness as independent diagnostic and prognostic tool in the evaluation of TCZ-treated patients. Despite limitations due to low number of enrolled patients and cross-sectional design, this study supports the role of German US7 score as a simple, reproducible and time-effective tool to monitor clinical and functional response in RA patients receiving TCZ. Disclosure of Interest: None declared